Down-Regulation of CK2α Leads toUp-Regulation of the Cyclin-Dependent Kinase Inhibitor p27KIP1 in Conditions Unfavorable for the Growth of Myoblast Cells. - Guerra, Barbara; Dembic, Maja; Siddiqui, Mohammad A.; Dominguez, Isabel; Ceppi, Paolo; Andresen, Brage S. (Cellular Physiology and Biochemistry, 2020)
BACKGROUND/AIMS: Compelling evidence indicates that CK2α, which is one of the two catalytic isoforms of protein kinase CK2, is required for cell viability and plays an important role in cell proliferation and differentiation. While much is known on CK2 in the context of disease states, particularly cancer, its critical role in non-cancerous cell growth has not been extensively investigated. METHODS: In the present study, we have employed a cell line derived from rat heart with inducible down-regulation of CK2α and CK2α-knockout mouse tissue to identify CK2-mediated molecular mechanisms regulating cell growth. For this, we have performed Incucyte® live-cell analysis and applied flow cytometry, western blot, immunoprecipitation, immunohistochemistry, RT-qPCR and luciferase-based methods. RESULTS: Here, we show that lack of CK2α results in significantly delayed cell cycle progression through G1, inhibition of cyclin E-CDK2 complex, decreased phosphorylation of Rb protein at S795, and inactivation of E2F transcription factor. These events are accompanied by nuclear accumulation and up-regulation of the cyclin-dependent kinase inhibitor p27KIP1 in cells and CK2α-knockout mouse tissues. We found that increased levels of p27KIP1 are mainly attributable to post-translational modifications, namely phosphorylation at S10 and T197 amino acid residues catalyzed by Dyrk1B and AMPK, respectively, as silencing of FoxO3A transcription factor, which activates CDKN1B the gene coding for p27KIP1, does not result in markedly decreased expression levels of the corresponding protein. Interestingly, simultaneous silencing of CK2α and p27KIP1 significantly impairs cell cycle progression without increasing cell death. CONCLUSION: Taken together, our study sheds light on the molecular mechanisms controlling cell cycle progression through G1 phase when myoblasts proliferation potential is impaired by CK2α depletion. Our results suggest that elevated levels of p27KIP1, which follows CK2α depletion, contribute to delay the G1-to-S phase transition. Effects seen when p27KIP1 is down-regulated are independent of CK2α and reflect the protective role exerted by p27KIP1 under unfavorable cell growth conditions.
EVALuna2:349298